Connecting the brain cholesterol and renin–angiotensin systems: potential role of statins and RAS‐modifying medications in dementia. (28th October 2018) - Petek, B.; Villa‐Lopez, M.; Loera‐Valencia, R.; Gerenu, G.; Winblad, B.; Kramberger, M. G.; Ismail, M.‐A.‐M.; Eriksdotter, M.; Garcia‐Ptacek, S.
Abstract: Millions of people worldwide receive agents targeting the renin–angiotensin system (RAS) to treat hypertension or statins to lower cholesterol. The RAS and cholesterol metabolic pathways in the brain are autonomous from their systemic counterparts and are interrelated through the cholesterol metabolite 27‐hydroxycholesterol (27‐OHC). These systems contribute to memory and dementia pathogenesis through interference in the amyloid‐beta cascade, vascular mechanisms, glucose metabolism, apoptosis, neuroinflammation and oxidative stress. Previous studies examining the relationship between these treatments and cognition and dementia risk have produced inconsistent results. Defining the blood–brain barrier penetration of these medications has been challenging, and the mechanisms of action on cognition are not clearly established. Potential biases are apparent in epidemiological and clinical studies, such as reverse epidemiology, indication bias, problems defining medication exposure, uncertain and changing doses, and inappropriate grouping of outcomes and medications. This review summarizes current knowledge of the brain cholesterol and RAS metabolism and the mechanisms by which these pathways affect neurodegeneration. The putative mechanisms of action of statins and medications inhibiting the RAS will be examined, together with prior clinical and animal studies on their effects on cognition. We review prior epidemiological studies, analysing their strengths and biases, and identify areas for future research. Understanding the pathophysiology of the brain cholesterol system and RAS and their links to neurodegeneration has enormous potential. In future, well‐designed epidemiological studies could identify potential treatments for Alzheimer's disease (AD) amongst medications that are already in use for other indications.